Silkworm model for Bacillus anthracis infection and virulence determination. Issue 1 (1st January 2021) - Paudel, Atmika; Furuta, Yoshikazu; Higashi, Hideaki
ABSTRACT: Bacillus anthracis is an obligate pathogen and a causative agent of anthrax. Its major virulence factors are plasmid-coded; however, recent studies have revealed chromosome-encoded virulence factors, indicating that the current understanding of its virulence mechanism is elusive and needs further investigation. In this study, we established a silkworm ( Bombyx mori) infection model of B. anthracis . We showed that silkworms were killed by B. anthracis Sterne and cured of the infection when administered with antibiotics. We quantitatively determined the lethal dose of the bacteria that kills 50% larvae and effective doses of antibiotics that cure 50% infected larvae. Furthermore, we demonstrated that B. anthracis mutants with disruption in virulence genes such as pagA, lef, and atxA had attenuated silkworm-killing ability and reduced colonization in silkworm hemolymph. The silkworm infection model established in this study can be utilized in large-scale infection experiments to identify novel virulence determinants and develop novel therapeutic options against B. anthracis infections.